Functional Outcome of Intramedullary Nailing with Rush Pin for Pediatric Both Bone Fractures of Forearm in Western Hilly Nepal - Shrestha, Rahul; Byanjankar, Subin; Dwivedi, Rajeev; Joshi, Ruban Raj; Ghimire, Mahesh Raj (Journal of Lumbini Medical College, 2017)
Introduction: Both bone diaphysis fracture of forearm is common in children of hilly area in Nepal because the children climbs tree and cliff for playing and cutting grass. Close reduction and casting is the preferred method of treatment these fractures but the chances of re-displacement is very high. Intramedullary nailing with titanium elastic nails or rush pins is widely accepted these days with good outcome. Titanium nails are popular in western world but is costly whereas rush pins are cheap and are preferred in developing world. The aim of this study was to evaluate the functional outcome of intramedullary rush pin for pediatric both bone fracture of forearm. Methods: In this retrospective, observational study done from 1st of February 2017 to 31st of March 2017, a total of sixty patients with both bone fractures of forearm were treated with intramedullary rush pin and followed up for six months for evaluation of functional outcome. T-test and Chi-square tests were done. Results: Closed reduction and internal fixation was done in 48 (80%) patients. Mean age of the patients was 9.23 year (SD=2.77). Fifty-six (93.3%) patients were male with a significant difference (p<0.001). With price et al. grading system, 49 (81.7%) patients had excellent results, nine (15%) had good and two (3.3%) patients had fair results. There was no major complication. Mean time to implant removal was 24.16 weeks (SD=1.62) from the time of surgery with range of 20 to 28 weeks. Among transverse and oblique fractures, patients with transverse fracture were likely to have better outcome (p=0.04). Conclusion: Intramedullary nailing with rush pin gives excellent to good functional outcome in majority of the cases without major complications at low cost for management of both bone fractures of forearm in children. Journal of Lumbini Medical College Vol 5, No 1, Jan-June 2017, Page: 23-28 DOI: https://doi.org/10.22502/jlmc.v5i1.106